Indo-Buddhist Borrowings in the Buryat Geseriad - Bair S. Dugarov (Монголоведение, 2022)
Introduction. The article examines an understudied issue of how and to what extent Buddhism had influenced the Buryat epic of Geser. Over the past two millennia, the Buddhist factor — starting from the Xiongnu era — has been to a certain degree reflected in various areas of spiritual life of Turko-Mongolian nomads and their descendants. Goals. So, the work aims to study impacts of Buddhism on such a significant monument of the Buryat oral poetic tradition as Geseriad. Results. The method of comparative analysis proves instrumental in identifying terms and concepts of Indo-Buddhist origin that constitute an ancient dimension in narrative structures of the uliger (epic). Those constants include as follows: hумбэр уула ‘Mount Sumeru’ associated with the world Mount Meru that serves to mark a center of the earth and universe in ancient Indian mythology; hун далай ‘milk sea’ that has an ancient Indian prototype in the Samudra Manthana episode. Similarly, some other cosmogonic concepts of ancient India — such as замби (Sanskr. Jambudvīpa ‘Jambu mainland’) and галаб (Sanskr. kalpa ‘aeon’) — had penetrated the Buryat folk mythological tradition through Buddhism to get completely absorbed and adapted. The Buryat Geseriad also contains traces of Indo-Buddhist mythology at the level of zoomorphic images, especially notable in the case of Khan Kherdig ‘king of birds and devourer of serpents’. Conclusions. The southern borrowings had become organically integral to the epic of Geser — its plot and images — so that nowadays tend to be perceived as quite ‘autochthonous’ and indigenous elements of the narrative. This circumstance attests to that Buddhist vestiges in the Buryat epic have a long history.